2013
DOI: 10.1186/1743-7075-10-39
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pre- and post-exercise consumption of multi-ingredient performance supplements on cardiovascular health and body fat in trained men after six weeks of resistance training: a stratified, randomized, double-blind study

Abstract: BackgroundThe cardiovascular (CV) and metabolic health benefits or risks associated with consumption of multi-ingredient performance supplements (MIPS) in conjunction with periodized resistance training (RT) in resistance-trained men are unknown. This population is a major target audience for performance supplements, and therefore, the purpose of this study was to investigate the combined effect of RT and commercially available pre- and post-exercise performance supplements on CV health and body fat in resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…However, when comparing pre−post intervention results for each way of measuring hypertrophy, both groups present significant increases for FFM (untrained: 1. 54 Performing a more detailed analysis of the training status on FFM, we found that the categories sedentary/untrained and physically active but no experience in RT, have higher and more significant values than the moderately trained (RT up to 1 year/intermediate, RT experience up to 2 years /intermediate, and RT experience up to 3 years/intermediate). Additionally, the highest values achieved are those obtained by the more experienced subjects, RT experience of 4 years or more/advanced (see Figure 4).…”
Section: Subgroup Analysismentioning
confidence: 78%
“…However, when comparing pre−post intervention results for each way of measuring hypertrophy, both groups present significant increases for FFM (untrained: 1. 54 Performing a more detailed analysis of the training status on FFM, we found that the categories sedentary/untrained and physically active but no experience in RT, have higher and more significant values than the moderately trained (RT up to 1 year/intermediate, RT experience up to 2 years /intermediate, and RT experience up to 3 years/intermediate). Additionally, the highest values achieved are those obtained by the more experienced subjects, RT experience of 4 years or more/advanced (see Figure 4).…”
Section: Subgroup Analysismentioning
confidence: 78%
“…Ad libitum on off days (post). 6 weeks of periodized resistance training (3 sessions/week) DEXA, POMS 3 ↑ FFM ( d = 0.22) ↔ FM ↔ POMS [ 65 ] Kedia et al 2014 43 resistance trained males and females Double-blind resistance training study using comparator control Prop. Blend 1: (4580 mg) Creatine Betaine Citrulline Dendrobium extract Caffeine *Comparator product matched for energy and caffeine content 30 min prior to exercise and with breakfast on off days.…”
Section: Chronic Effects Of Mips On Performancementioning
confidence: 99%
“…Some studies have documented improvements in subjective feelings of energy and focus [ 91 , 92 ], while Gonzalez et al [ 98 ] did not. When taken chronically for a period of 4 to 8 weeks, multi-ingredient pre-workout supplements have been shown to increase measures of strength [ 93 , 94 , 97 ], power output [ 96 ], and lean mass [ 93 95 ]. In contrast, Outlaw et al [ 99 ] found no significant benefit for body composition, strength, or power output with ingestion of a multi-ingredient supplement versus placebo.…”
Section: Introductionmentioning
confidence: 99%